A 300 nm thick epitaxial AlInN film with a highly flat surface grown almost perfectly lattice-matched to c-plane free-standing GaN substrate. (16th April 2019) - Miyoshi, Makoto; Yamanaka, Mizuki; Egawa, Takashi; Takeuchi, Tetsuya
Abstract: Single-layer AlInN films with a film thickness of approximately 300 nm were grown on a c- plane free-standing (FS) GaN substrate by metalorganic chemical vapor deposition. The result showed that a highly flat-surface AlInN film with a small root-mean-square surface roughness of less than 0.5 nm was realized by adjusting its alloy composition to an almost perfectly lattice-matched to FS-GaN. As for the highly flat-surface AlInN film, the optical constants were evaluated in whole visible wavelength by spectroscopic ellipsometry. Then, its energy bandgap energy was determined to be 3.92 eV.